Alienação fiduciária em garantia de bem imóvel: uma análise comparada - Negrato, Gustavo Scudeler (2010)
After twelve years since the approval of the Law of Real Estate Financing System (9,514/97) many controversial issues remain, either in doctrine or in case law, regarding the contractual form that established the new in rem guarantee right, extending the fiduciary property to real estates. The purpose of this thesis is to examine the main aspects of the fiduciary assignment for the guarantee of real estates, in order to improve the understanding of the concept of such institute. The prospect adopted is the comparative law, analyzing the origin of fiduciary business by means of the fiducia of Roman law, the pledge of Germanic law, the trust of Anglo-Saxon law, the use of atypical fiduciary business in modern law by countries with Roman tradition and, finally, the institute as regulated in Brazilian law. The main conclusions appoint the unique character of the fiduciary assignment adopted by the Brazilian legislation, despite the undeniable influence of foreign law, indicating the solution for controversial questions regarding the institute, its finalities and consequences. It concludes for the constitutionality of the procedure for extrajudicial execution established by the law under discussion, its compability with standards of the Code of Consumer Protection, and the impossibility of determining the civil prision of fiduciant, because of the recent case-law in the Supreme Court Federal and Superior Court of Justice